Flow-cytometric analysis of immune cell populations in patients with depression: relationship with depression severity and electroconvulsive therapy therapeutic outcomes - Ryan, Karen M.; O’Rourke, Aoife; Sheridan, Christopher; Balcells Quintana, Marina; Moran, Barry; Fletcher, Jean M.; McLoughlin, Declan M.; Harkin, Andrew (Frontiers in Cellular Neuroscience, 2025)
IntroductionImmunological changes are implicated in the pathophysiology of depression. We aimed to assess phenotype and frequency of immune cell subtypes, including an assessment of regulatory T cells and production of cytokines by T cell subsets following stimulation.MethodsUsing a flow cytometric analysis, peripheral blood samples obtained from medicated patients with depression (n = 20) were analysed and compared to age-and sex-matched healthy controls (n = 21), and in patients with depression after electroconvulsive therapy (ECT) in a real-world clinical setting. Depression severity was assessed using the Hamilton Depression Rating Scale (HAM-D24).ResultsA reduction in the frequencies of CD19+ B cells and IL-17+ CD8 T cells was evident in depressed patients compared to healthy controls. For a subgroup of depressed patients assessed pre- versus post-ECT, there was no change in phenotype, frequency or function of immune cell subtypes within 72 hours of completing treatment. Further exploratory analyses found that baseline CD16-CD14+ classical monocyte frequency correlated with change in HAM-D24 score post-ECT, indicating that a higher frequency of classical monocytes at baseline is associated with greater symptom improvement after treatment. A reduced number of CCR7-CD45RO+ effector memory T cells was also found to be associated with an improvement in symptoms post-ECT.DiscussionOverall, these results demonstrate that flow cytometry is useful for immune profiling to identify altered adaptive immune features in depression and potential biomarkers of ECT response. In particular, changes in classical monocytes and effector memory T cells were associated with treatment response in patients with unipolar depression.